Altered Brain Function and Causal Connectivity Induced by Repetitive Transcranial Magnetic Stimulation Treatment for Major Depressive Disorder - Guan, Muzhen; Wang, Zhongheng; Shi, Yanru; Xie, Yuanjun; Ma, Zhujing; Liu, Zirong; Liu, Junchang; Gao, Xinyu; Tan, Qingrong; Wang, Huaning (Frontiers in Neuroscience, 2022)
Objective: Repetitive transcranial magnetic stimulation (rTMS) can effectively improve depression symptoms in patients with major depressive disorder (MDD); however, its mechanism of action remains obscure. this study explored the neuralimaging mechanisms of rTMS in improving depression symptoms in patients with MDD. Methods: In this study, MDD patients with first-episode, drug-naive (n = 29) and healthy controls (n = 33) were enrolled. Resting-state functional magnetic resonance imaging (rs-fMRI) data were collected both before and after the treatment. the amplitude of the low-frequency fluctuation (ALFF) and regional homogeneity (ReHo) were analysed. The brain region with synchronous changes was selected as the seed point, and the differences in the causal connectivity between the seed point and whole brain were investigated via Granger causality analysis (GCA). Results: After the rTMS treatment, the ALFF was significantly increased in the left superior frontal gyrus (p < 0.01) and decreased in the left middle frontal gyrus and left precuneus (p < 0.01). Furthermore, ReHo was significantly increased in the left middle frontal and left middle occipital gyri (p < 0.01) in patients with MDD. Before treatment, GCA using the left middle frontal gyrus (the brain region with synchronous changes) as the seed point revealed a weak bidirectional causal connectivity between the middle and superior frontal gyri as well as a weak causal connectivity from the inferior temporal to the middle frontal gyri. After treatment, these causal connectivities were strengthened. Moreover, the causal connectivity from the inferior temporal gyrus to the middle frontal gyri negatively correlated with the total HAMD-17 score (r = −0.443, p = 0.021). Conclusion: rTMS treatment not only improves the local neural activity in the middle frontal gyrus, but also strengthens the bidirectional causal connectivity between the middle and superior frontal gyri and the causal connectivity from the inferior temporal to the middle frontal gyri. Changes in these neuroimaging indices may represent the neural mechanisms underlying rTMS treatment in MDD.